ANALISIS PERBANDINGAN BIAYA OPERASIONAL ALAT BERAT MILIK SENDIRI DENGAN BIAYA SEWA ALAT BERAT PADA PROYEK PELEBARAN JALAN PEMENANG-BAYAN I KABUPATEN LOMBOK UTARA - HASYIM, HASYIM; SUTEJA, I WAYAN; ROHANI, ROHANI; VALENTINA, YUVITA (Ganec Swara, 2025)
The Pemenang-Bayan I road widening project in North Lombok Regency is part of the government's initiative to improve transportation infrastructure to support local economic growth and facilitate community mobilization. One of the biggest cost components in infrastructure projects is the operational cost of heavy equipment. In the implementation of this project, contractors have two alternatives in meeting the needs of heavy equipment, namely using their own heavy equipment or renting from a third party. This study aims to analyze the comparison between the operating costs of own heavy equipment and the cost of renting heavy equipment, focusing on two main types of heavy equipment, namely excavators and vibro compactors. This study uses interview techniques to collect analysis data. Data analysis was carried out to obtain a comparison of operational costs between the use of own equipment and equipment rental. Based on the calculation of total operational costs for earthworks in segment one (STA 0+00 - STA 1+185) of the Pemenang-Bayan I Road Widening Project, the use of self-owned heavy equipment is more economical for excavators, where the use of self-owned equipment can save operational costs of around 13.5% (Rp.2 .891,170.00 to Rp.4,336,755.00) compared to rental equipment from Cv Prayoga and save about 26% (Rp.6,723,932.00 to Rp.10,085,899.00) when compared to rental equipment from PT Trakindo Utama. As for the Vibro Compactor , the use of rental equipment is more economical than the use of self-owned equipment, which saves about 2.5% (Rp.73,479.00 to Rp.110,219.00) of the total operational cost.